Evidence of a Relationship Between Plasma Leptin, Not Nesfatin-1, and Craving in Male Alcohol-Dependent Patients After Abstinence - Xu, Ya-Yun; Ge, Jin-Fang; Chen, Jun; Liang, Jun; Pang, Liang-Jun; Gao, Wen-Fan; Cao, Yin; Shan, Feng; Liu, Yang; Yan, Chun-Yu; Xia, Qing-Rong (Frontiers in Endocrinology, 2020)
The goal of this study was to determine whether the plasma leptin, nesfatin-1, cortisol, brain-derived neurotrophic factor (BDNF), and inflammatory cytokines could be used as potential biomarkers for the degree of craving in the alcohol-dependent patients after 1 month of abstinence. A total of 83 patients with alcohol use disorder (AUD) and 61 healthy subjects were assessed. Patients with AUD were selected from Department of Material Dependence, Anhui Mental Health Center, and subjects in the control group were selected from healthy volunteers. The Alcohol Urge questionnaire Scale (AUQ) was used to evaluate the extent of craving for alcohol, and the Michigan Alcoholism Screening Test (MAST), the Fagerstrom Test for Nicotine Dependence (FTND), the Self-Rating Anxiety Scale (SAS) and the Self-Rating Depression Scale (SDS) were also assessed in patients with AUD. Enzyme-Linked Immunosorbent Assay (ELISA) was used for the measurement of plasma leptin, nesfatin-1, cortisol, BDNF, Interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor-α (TNF-α) levels. Compare with healthy controls, the average leptin, leptin/BMI, IL-6, CRP, and TNF-α levels in patients with AUD were significantly increased, while the BDNF levels were significantly decreased. Moreover, the partial correlational analysis showed that the AUQ scores of the alcohol-dependent patients were positively correlated with the plasma leptin levels (r = 0.613, P < 0.001), rather than nesfatin-1 (r = 0.066, P = 0.569) after controlling for age as covariate. Furthermore, plasma nesfatin-1 levels were found to be correlated with the SDS scores (r = 0.366, P = 0.001) in the AUD group. In addition, plasma leptin levels were positively associated with the plasma IL-6 (r = 0.257, P = 0.033), CRP (r = 0.305, P = 0.011), and TNF-α (r = 0.311, P = 0.009) levels, and negatively associated with the BDNF levels (r = -0.245, P = 0.042) in patients with AUD. These results suggest that plasma leptin, but not nesfatin-1, might be a potential biomarker for the degree of craving in alcohol-dependent patients after 1 month of abstinence, the mechanism of which might be related to the dysfunction of the inflammatory cytokines and BDNF levels.